Achieving high selectivity for nitrate electrochemical reduction to ammonia over MOF-supported RuxOy clusters. Issue 8 (21st January 2022) - Qin, Jiangzhou; Wu, Kun; Chen, Liuzhou; Wang, Xintao; Zhao, Quanlin; Liu, Baojun; Ye, Zhengfang
Abstract : Nitrate (NO3 − ) electroreduction to ammonia (NH4 + ) is a sustainable alternative strategy for NH4 + synthesis, and it can be used to solve the water pollution problem by simultaneously turning waste into high-value ammonia. Abstract : Nitrate (NO3 − ) electroreduction to ammonia (NH4 + ) is a sustainable alternative strategy for NH4 + synthesis, and it can be used to solve the water pollution problem by simultaneously turning waste into high-value ammonia. However, the conversion of NO3 − into NH4 + involves multi-electron transfer reactions that could generate a series of nitrogen oxyanions and hydrogen as undesired byproducts. The design of efficient catalysts to selectively transform NO3 − into NH4 + is, therefore, highly needed. In this work, we report Ru x O y clusters stabilized on nickel metal–organic frameworks (RuNi-MOFs) and evaluate their electrocatalytic NO3 − reduction performance. The catalyst exhibits nearly 100% NH4 + selectivity with an NH4 + –N yield rate of up to 274 μg h −1 mgcat. −1 at −1.7 V vs. Ag/AgCl, and a maximal NH4 + faradaic efficiency (FE) of ∼73% at −1.2 V vs. Ag/AgCl. The theoretical calculations show that the NO2 − intermediate is easily further reduced to NH4 +, and could maintain nearly 100% NH4 + selectivity. This novel strategy will provide a new idea for green ammonia synthesis.